Research of WLAN authentication in roaming environment with the trend of network integration - Zhang-zhe LIU; Hua-ying SHU (Tongxin xuebao)
In the tendency of network convergence,the method of WLAN network client authentication based on telecommunications network will be the main way of WLAN authentication in the future.In order to make WLAN authentication efficiency and security under roaming condition,WLAN authentication requirements were analyzed,the authentication mode,the process and the existing problems were discussed.An application model and design scheme of WLAN network client authentication based on EAP SIM/AKA protocol with the trend of network integration were proposed and verified.Experimental results show that this application model can complete the EAP SIM/AKA protocol identification of a WLAN client in roaming process,reduce the investment of networks,keep the safety grades of the nodes in the visited WLAN with the initial safety grades,and realize the real-time charging.